The 13 November 2007 rock-fall at Viale Tiziano in Rome (Italy) - M. Amanti; V. Chiessi; P. M. Guarino (Natural Hazards and Earth System Sciences, 2012)
The aim of the study was to perform a study on the western slope of the Monti Parioli hill (Rome, Italy) affected by frequent rock-fall phenomena, such as the one that occurred on 13 November 2007. This goal was achieved by defining a detailed reconstruction of the stratigraphical, geological and geomechanical structure of the slope and by conducting a back-analysis of the rock-fall event using 2-D and 3-D modeling tools. The reconstruction of the slope's geological structure, characterized by the presence of two anthropogenic cavity systems, and the characterisation of geomechanical properties of outcropping terrains have been realized by means of a detailed geological survey and a campaign of direct and indirect investigations. Therefore, continuous rotary, coring boreholes up to 60 m, collecting undisturbed samples for laboratory tests and performing direct investigations such as SPTs and pressuremeter tests were carried out. The indirect investigations included electrical tomography surveys, linear surface seismic refraction surveys and seismic cross-hole tests. Using the reconstructed geological-technical model, it was possible to define the stability conditions of the slope at the time of collapse by using a computational two-dimensional explicit finite difference program (FLAC) and a 3-D finite element analysis (FEMLAB).